PENGEMBANGAN PROGRAM PENDIDIKAN DI SD ISLAM INTERNASIONAL AL-ABIDIN SURAKARTA DALAM MENGHADAPI MEA - Amalia, Tsabita Fiki; Sayekti, Ika Candra (Universitas Muhammadiyah Surakarta, 2016)
ASEAN Economic Community (AEC) ia an integratied system of the countries in Southeast Asia that enable and facilitate the free trade system. Since 2015 the AEC has been officially started, and many foreign companies has been opened in Indonesia. However, the quality of Human Resources (HR) in Indonesia is lacking to confront AEC’s system. It can be seen from the number of unemployed people in Indonesia and Indonesian citizen education level is still low. This shows a lack of quality in education. Departing from this problem, the authors conducted research at the international elementary school, SDII Al Abidin Surakarta. This school has excellent programs that can be developed and replicated in order to improve the quality of Human Resources (HR) since elementary school. This research aims to study programs that are run in order to deal with AEC. This research was conducted with a qualitative descriptive method by collecting data through interviews, observation, and documentation. The results showed some excellent programs that are owned by SDII Al Abidin Surakarta which can be used as a weapon to face the ASEAN Economic Community (AEC). The programs are international curriculum, three varians grade programs, and extracurricular.